Immunology / BIOS Instant Notes - Lydyard, Peter M. (BIOS instant notes., 2011)
"BIOS Instant Notes in Immunology, Third Edition, is the perfect text for undergraduates looking for a concise introduction to the subject, or a study guide to use before examinations. Each topic begins with a summary of essential facts-an ideal revision checklist-followed by a description of the subject that focuses on core information, with clear, simple diagrams that are easy for students to understand and recall in essays and exams"--